Hay part air cassava and enzymes in pig power stages of growth and termination - Emanuela Lima de Oliveira (2015)
Three experiments were conducted involving 78 pigs castrated males of commercial line. In the first experiment were used 16 animals with average weight of 23.94 Â 0.63 kg, in order to evaluate the chemical composition and nutrient digestibility, nitrogen balance and determination of digestible and metabolizable energy HSC for pigs . The animals were housed in metabolic cages and distributed in two treatments: control diet and food testing, the latter being composed of 70% of the control diet and 30% of HSC. Each treatment with 8 replicates. Although the FPAM have adequate Chemical Composition has low-energy 1,142 kcal / ME / kg and based on this result rations of other experiments were calculated. Nitrogen balance was affected by the inclusion of HSC. In the second experiment, we used 30 pigs with average weight of 22.73 Â 1.79 kg, with the objective of evaluating increasing levels of HSC in diets for growing and finishing pigs on performance, digestibility of feed, carcass characteristics , color and pH of the meat and bioeconomic evaluation of rations. 5 treatments were used, considering increasing levels of HSC 0; 3; 6; 9:12% and 6 replicates per treatment. Increasing levels of HSC affected the performance by detecting downward linear effect for feed intake increased as the inclusion of the ingredient, reflecting positively a better conversion in the growth phase II. It reiterated that the inclusion of 12% of HSC improves the ether extract digestibility coefficients, neutral detergent fiber and gross energy of the feed. It was found that the inclusion of HSC did not affect carcass characteristics, color and pH of animal meats. There was a decreasing linear effect for all economic variables of the growth phase II, except for the economic efficiency ratio which found increasing linear effect. In the finishing phase was quadratic effect for economic efficiency ratio and average cost ratio of feed consumed and decreasing linear effect for partial gross revenue. In the third experiment, we used 32 pigs live weight of 22.64 Â 0.63 kg for evaluating the inclusion of HSC in diets with or without addition of an enzyme supplement composed of xylanase, glucanase and mannanase on digestibility of diets, blood concentrations of triglycerides and urea, performance, carcass characteristics and bioeconomic evaluation of rations. 4 treatments were used: control diet, 12% inclusion of HSC, 12% inclusion of HSC with reduced energy matrix in 100 kcal / kg with and without addition of enzyme complex with 8 replicates per treatment. Enzyme supplementation did not improve the digestibility of nutrients and energy. The inclusion of the ingredient reduced the level of serum urea in all evaluated phases. There were no treatment effects for growth performance, carcass characteristics and bioeconomic evaluation of rations. The inclusion of 12% of HSC without enzyme supplementation can be an economically viable food alternative in the production of pigs for slaughter.